Cross-selling in Colombian pension funds: An approach using survival analysis (2011)
The development of commercial strategies for effective cross-sell pension services may be one of the biggest challenges of pension funds. The database of the affiliates of a Colombian mandatory pension fund was used to implement several models that describe the incidence of 4 characteristics of affiliates on the probability of entering the voluntary pension fund in the following month. The models are based on the survival analysis techniques.